ON THE JESUS PRAYER - VRYZAS, Peter (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
This paper focuses on the Jesus Prayer, attempting to explain (1) how in this prayer, by the grace of God, our mind can be united with the heart and (2) what the fruits of this marvellous union are.